Purchasing and supply management - Johnson, P. Fraser (New York, NY : McGraw Hill, 2024)
"Purchasing and supply management has become increasingly visible in a world where supply is a major determinant of corporate survival and success. Supply chain performance influences not only operational and financial risks but also reputational risk. Extending the supply chain globally into emerging regions places new responsibilities on the supplier and supply, not only to monitor environmental, social, political, and security concerns but also to influence them"--
Purchasing and Supply Management -- Supply Strategy -- Supply Organization -- Supply Processes and Technology -- Make or Buy, Insourcing, and Outsourcing -- Need Identification and Specification -- Quality -- Quantity and Inventory -- Delivery -- Price -- Cost Management -- Supplier Selection -- Supplier Evaluation and Supplier Relationships -- Global Supply Management -- Legal and Ethics -- Other Supply Responsibilities -- Supply Function Evaluation and Trends.
Includes index.
Keywords: Industrial procurement; Materials management